PENGARUH DOSIS INOKULAN ALAMI (EKTOMIKORIZA) TERHADAP PERTUMBUHAN SEMAI TENGKAWANG (Shorea pinanga) - . Gusmiaty; Muh. Restu; Ayu Lestari (Forestry Faculty of Universitas Hasanuddin, 2012)
This research aimed to know the effect of some doses of natural inoculants on the growth of Shorea pinanga seedling. The research was carried out with several steps including seed provision, inoculation of ectomycorrhyza, planting and maintenance in the nursery. The result of the research showed that height and number of branches were different at the significant level of 5 %, while diameter and number of leaves were not significantly different. The natural inoculants dose of 15 g showed the best growth in response to the increment of height, diameter, and number of leaves, while that of 20 g showed the best in the number of branches increment. Key words: Shorea pinanga, ectomycorrhyza, seedling, natural inoculantstor, Local Government Revenue, regional autonomy